Brain alterations of regional homogeneity, degree centrality, and functional connectivity in vulnerable carotid plaque patients with neither clinical symptoms nor routine MRI lesions: A resting-state fMRI study - Wang, Qian; Xing, Wu; Ouyang, Lirong; Li, Lang; Jin, Hong; Yang, Shuai (Frontiers in Neuroscience, 2022)
Aims: Based on resting-state functional MRI (fMRI), we preliminarily explored brain alterations in asymptomatic patients with carotid vulnerable plaques but carotid stenosis < 50%. Methods: A total of 58 asymptomatic patients with carotid vulnerable plaques (stenosis < 50%) and 38 healthy controls were recruited. Between-group differences in regional homogeneity (ReHo), degree centrality (DC), and functional connectivity (FC) were analyzed. Correlation analysis was performed between the ReHo or DC values in altered brain regions as well as voxel-wise abnormal FC and scores on neuropsychiatric scales, serum interleukin-6 (IL-6) and C-reactive protein (CRP). Results: Both ReHo and DC values on the left superior occipital gyrus (SOG.L) of the asymptomatic carotid vulnerable plaque group reduced regardless of plaque location (left, right or bilateral). Functional connections weakened between SOG.L and right lingual gyrus (LING.R)/right inferior occipital gyrus (IOG.R), right middle frontal gyrus (MFG.R)/orbital part superior frontal gyrus (ORBsup.R)/orbital part middle frontal gyrus (ORBmid.R), left precentral gyrus (PreCG.L)/postcentral gyrus (PoCG.L), PreCG.L, left supplementary motor area (SMA.L), right paracentral lobule (PCL.R), left precuneus (PCUN.L), and right postcentral gyrus (PoCG.R)/ PCL.R. In ReHo-altered brain regions, ReHo values were positively correlated with Hamilton Rating Scale for Depression (HAMD) scores, and setting region of abnormal ReHo as seed points, voxel-wise FC between SOG.L and PreCG.L was negatively correlated with CRP. Conclusions: Cerebral alterations of neuronal synchronization, activity and connectivity properties in asymptomatic carotid vulnerable-plaque group were independent of the laterality of carotid vulnerable plaques. Significant relation between ReHo values on the SOG.L and HAMD indicated that even when there were neither clinical symptoms nor lesions on routine MRI, brain function might have changed already at early stage of carotid atherosclerosis. Inflammation might play a role in linking carotid vulnerable plaques and changes of resting state functional connectivity.